The Impact of Flexibility and Arm Strength on Basketball Three-Point Shooting Performance - Gigih Siantoro (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Basketball is a multifaceted game that relies on various physical components to score points by shooting the ball through the hoop. Different types of shots exist, including the three-point shot. Optimal shooting requires support from physical elements such as flexibility and arm strength. Therefore, this study seeks to establish the relationship between flexibility, arm strength, and three-point shooting performance in basketball. Materials and methods. The research method employed in this study is correlation research. A purposive random sampling technique was used to select 32 athletes for the sample. Data collection took place in a single meeting. The instruments utilized in this research included the push and pull dynamometer, goniometer, and three-point test. Following data collection, a correlation test data analysis will determine the relationship between one or more variables and other variables. Results. The results of the correlation test indicate a significant relationship between flexibility, arm strength, and three-point shooting accuracy. The test showed a statistically significant correlation with a p-value of 0.00, which is less than the standard threshold of 0.05. Conclusion. The research concludes that the success of three-point shots in basketball is influenced by physical components such as flexibility and arm strength. Therefore, improving these components can lead to better shooting results.